2019
DOI: 10.1177/1753466619888127
|View full text |Cite
|
Sign up to set email alerts
|

Repository corticotropin injection in patients with advanced symptomatic sarcoidosis: retrospective analysis of medical records

Abstract: Background:Repository corticotropin injection (RCI) has regulatory approval for many indications, including symptomatic sarcoidosis. This large case series of patients with advanced symptomatic sarcoidosis treated with RCI describes patient characteristics, RCI utilization patterns, concomitant therapies, and physicians’ assessments of treatment response.Methods:Patients ⩾18 years with symptomatic sarcoidosis, treated with RCI in the previous 36 months, who had completed a course of RCI or received RCI for ⩾6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 15 publications
3
40
0
Order By: Relevance
“…This study did not analyze daily dose changes of glucocorticoids that could have been impacted by RCI treatment as assessed in previous studies. 30 , 32 Taken together, we observed changes in standard RA treatments that were sustained for up to 1 year after RCI initiation that are consistent with the improvements in clinical measures of disease severity and PROs.…”
Section: Discussionsupporting
confidence: 75%
“…This study did not analyze daily dose changes of glucocorticoids that could have been impacted by RCI treatment as assessed in previous studies. 30 , 32 Taken together, we observed changes in standard RA treatments that were sustained for up to 1 year after RCI initiation that are consistent with the improvements in clinical measures of disease severity and PROs.…”
Section: Discussionsupporting
confidence: 75%
“…In clinical settings, it is often used after other therapies have failed. 22,23 Due to this unique place in therapy, the literature contains very little information about the profile of patients who would benefit most from RCI therapy or how the therapies are used. Therefore, it is imperative to describe these aspects of real-world data to help ensure appropriate use.…”
Section: Introductionmentioning
confidence: 99%
“…The study also found that an RCI dosage of 40 units twice a week was as effective as 80 units and appeared to be better tolerated [17]. In another retrospective study, CHOPRA et al [24] reviewed 302 sarcoidosis patients and reported that >90% had improvement of their symptoms. Note that this study had not yet been published when the Delphi panels were conducted.…”
Section: Discussionmentioning
confidence: 90%